Pengaruh Mekanisme Corporate Governance, Ukuran Perusahaan, dan Leverage Terhadap Praktik Manajemen Laba pada Perusahaan Sektor Industri Manufaktur di Bursa Efek Indonesia Periode 2005-2008 - Isbanah, Yuyun (BISMA (Bisnis dan Manajemen), 2018)
The objectives of the research is to empirically examine the influence of corporate governance, firms size, and firms leverage to earnings management practice. Corporate governance is proxied by managerial ownership, institutional ownership, sense of independent of director, and size of board director. Firms size is measured with logarithm of total assets. The firms leverage is proxied by total debt to total assets ratio. To detect earnings management this research using discretionary accruals (managed accruals) that measured with modified Jones models. The sample used in this research is manufacture companies that implement corporate governance and registered in Indonesia Stock Exchange during 2005 until 2008. The method of analysis of this research used multi regression. Result of this research shows that: (1) Simultaneously of institutional ownership, managerial ownership, presence of independent of director, size of director, size, and leverage have significant influence to earnings management. (2) Managerial ownership had not influence earnings management. (3) Institutional ownership had not influence earnings management. (4) Presence of independent of director had negatively influence earnings management. (5) Size of director had negatively influence earnings management. (6) Size had positively influence earnings management. (7) Leverage had negatively influence earnings management